Comparison of Doppler echocardiographic methods with heart catheterisation in assessing aortic valve area in 100 patients with aortic stenosis. Issue 3 (March 1995) - Fischer, J. L.; Haberer, T.; Dickson, D.; Henselmann, L.
Abstract : OBJECTIVE--To examine the practicability and accuracy of Doppler echocardiographic methods in determining aortic valve area. METHODS--Aortic valve areas determined by three methods using Doppler echocardiography (applying the continuity equation and the modified Gorlin formula using data from Doppler echocardiography and right heart catheterisation) were compared with values obtained by heart catheterisation. PATIENTS--100 consecutive patients with aortic stenosis aged between 34 and 83 years (mean (SD) 66 (10)). RESULTS--Differences in individual patients' measurements of aortic valve area by the three Doppler techniques varied by up to 0.56 cm2 compared with values obtained by heart catheterisation. On average, values obtained from Doppler echocardiographic methods lay up to 51% below and 78% above those obtained by heart catheterisation. CONCLUSIONS--All three Doppler echocardiographic methods were practicable in routine clinical practice for patients of all ages, but they were of limited accuracy when compared with the aortic valve areas found invasively using the invasive Gorlin equation. However, these deviations may not always be due to inadequacies of the Doppler methods: they could also be caused by limitations in the Gorlin formula. Doppler methods can be repeated if required, they allow examination of the morphology of the valve, and they subject the patient to considerably fewer risks than the invasive procedure. An adequate strategy in determining the severity of aortic valve stenosis would be to calculate the valve area by Doppler echocardiography as well as considering the valvar aortic pressure gradient. The valve area alone should not be relied on exclusively, as has been the increasing practice in the past few years.